ASSUMPTIONS ON SOCIAL SUCCESS AND MOTIVATION IN YOUTHFUL AGE - Kobzeva, Olga; Tuzova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The problem of social success has not been considered as an independent one in Psychology for a long time, but it has been included in the structure of research related to effective communication, social status and professional competence. The increased interest in it is due to the growing attention to the problem of personality changes, an increase in the environmental “challenges” to human abilities, as well as the need to quickly respond to changes in society. The authors study the role of social success in the structure of mental development of the personality; define the determinants that affect its formation and development. The purpose of research is to study the correlation between the level of motivation for success and assumptions on social success among youthful age. The study involved 258 respondents (99 young men and 159 young ladies aged 18 to 21 years). The researchers used a psychodiagnostic method, including two techniques (the “Successful person” method by G.R. Khuzeeva, the method of diagnosing motivation for success by T. Ehlers, in adaptation of E.P. Belinskaya), methods of mathematical and statistical analysis, a genetic method. The results of the study showed that the assumptions on social success in youthful age is associated with getting education, self-confidence, determination, hard work. The authors revealed the relationship between the learners’ level of motivation for success and their assumptions on social success. In a group of young men with a high level of motivation for success, assumptions on social success are associated with the activity aspect (diligence, one’s own activity, responsibility) and the humanistic orientation (well-disposed, responsive, able to sacrifice). Respondents with a low level of motivation for success have a material orientation in the image of success (careerist, entrepreneurial, has connections with the right people).